Perancangan Video Digital Motion Graphic 2D untuk Promosi Perpustakaan Menggunakan HMDM - Edy Jogatama Purhita; Auliya Silvi Rahmawati; Ayyub Hamdanu Budi Nurmana Slamet (STEKOM PRESS, 2022)
The Boyolali Regional Library is a means of supporting public education organized by the Government of Boyolali Regency, Central Java. It is necessary to design promotional media and library information in order to increase public interest in coming and getting to know the complete library facilities. This research designs multimedia in the form of 2D digital motion graphic video as a promotional media for the Boyolali regional library. The method used is the Holistic Multimedia Development Model (HMDM) development model whose multimedia development stage considers the guiding aspects of multimedia quality. The results of the media expert and material expert validation test with a score of 85% and 90%, respectively. While in the user test, the positive response was 86%. So that the results of multimedia design are in the very good category and in line with expectations.